Recurrent Lobar Hemorrhages and Multiple Cortical Superficial Siderosis in a Patient of Alzheimer's Disease With Homozygous APOE ε2 Allele Presenting Hypobetalipoproteinemia and Pathological Findings of 18F-THK5351 Positron Emission Tomography: A Case Report - Ikeda, Masaki; Okamoto, Koichi; Suzuki, Keiji; Takai, Eriko; Kasahara, Hiroo; Furuta, Natsumi; Furuta, Minori; Tashiro, Yuichi; Shimizu, Chisato; Takatama, Shin; Naito, Isao; Sato, Mie; et al. (Frontiers in Neurology, 2021)
In Alzheimer's disease, the apolipoprotein E gene (APOE) ε2 allele is a protective genetic factor, whereas the APOE ε4 allele is a genetic risk factor. However, both the APOE ε2 and the APOE ε4 alleles are genetic risk factors for lobar intracerebral hemorrhage. The reasons for the high prevalence of lobar intracerebral hemorrhage and the low prevalence of Alzheimer's disease with the APOE ε2 allele remains unknown. Here, we describe the case of a 79-year-old Japanese female with Alzheimer's disease, homozygous for the APOE ε2 allele. This patient presented with recurrent lobar hemorrhages and multiple cortical superficial siderosis. The findings on the 11C-labeled Pittsburgh Compound B-positron emission tomography (PET) were characteristic of Alzheimer's disease. 18F-THK5351 PET revealed that the accumulation of 18F-THK 5351 in the right pyramidal tract at the pontine level, the cerebral peduncle of the midbrain, and the internal capsule, reflecting the lesions of the previous lobar intracerebral hemorrhage in the right frontal lobe. Moreover, 18F-THK5351 accumulated in the bilateral globus pallidum, amygdala, caudate nuclei, and the substantia nigra of the midbrain, which were probably off-target reaction, by binding to monoamine oxidase B (MAO-B). 18F-THK5351 were also detected in the periphery of prior lobar hemorrhages and a cortical subarachnoid hemorrhage, as well as in some, but not all, areas affected by cortical siderosis. Besides, 18F-THK5351 retentions were observed in the bilateral medial temporal cortices and several cortical areas without cerebral amyloid angiopathy or prior hemorrhages, possibly where tau might accumulate. This is the first report of a patient with Alzheimer's disease, carrying homozygous APOE ε2 allele and presenting with recurrent lobar hemorrhages, multiple cortical superficial siderosis, and immunohistochemically vascular amyloid β. The 18F-THK5351 PET findings suggested MAO-B concentrated regions, astroglial activation, Waller degeneration of the pyramidal tract, neuroinflammation due to CAA related hemorrhages, and possible tau accumulation.